When do we need more than local compression to control intraoral haemorrhage? - Sohn, Jun-Bae (J Korean Assoc Oral Maxillofac Surg, 2019)
OBJECTIVES: The aims of this study were to determine the effectiveness of local compression in patients presenting to the emergency room with intraoral bleeding and to identify when complex haemostatic measures may be required. MATERIALS AND METHODS: Five hundred forty patients who had experienced intraoral haemorrhage were retrospectively reviewed. The outcome variable was the haemostasis method used, i.e., simple (local compression with gauze) or complex (an alternative method after local compression has failed). Predictor variables were sex, age, American Society of Anesthesiologists (ASA) class, hepatic cirrhosis, bleeding disorder, use of antithrombotic agents, and site/cause of haemorrhage. RESULTS: The mean patient age was 48.9±23.9 years, 53.5% were male, 42.8% were ASA class II or higher, and 23.7% were taking antithrombotic agents. Local compression was used most often (68.1%), followed by local haemostatic agents, sutures, systemic tranexamic acid or blood products, and electrocautery. The most common site of bleeding was the gingiva (91.7%), and the most common cause was tooth extraction (45.7%). Risk factors for needing a complex haemostasis method were use of antithrombotic agents (odds ratio 2.047, P=0.009) and minor oral surgery (excluding extraction and implant procedures; odds ratio 6.081, P=0.001). CONCLUSION: A haemostasis method other than local compression may be needed in patients taking antithrombotic agents or having undergone minor oral surgery.